Design, synthesis and evaluation of novel angiotensin II receptor 1 antagonists with antihypertensive activities. Issue 42 (17th May 2017) - Bao, Xiao-Lu; Zhu, Wei-Bo; Shan, Tian-Li; Wu, Zhuo; Zhang, Rui-Jing; Liao, Ping-Yong; Zheng, Mei-Zhen; Tang, He-Sheng; Yan, Yi-Jia; Chen, Zhi-Long
Abstract : A novel Ang II receptor 1 antagonist1f was found to be an efficient, long-acting and safe antihypertensive drug candidate. Abstract : A series of novel angiotensin II receptor 1 antagonists (1a–f, 2a–f ) were designed, synthesized and evaluated. Radioligand binding assays showed that all these prepared compounds displayed nanomolar affinity for angiotensin II type 1 receptor, among which compound1f was more affinitive than telmisartan at the same order of magnitude with an IC50 value of 1.13 ± 1.68 nM. The antihypertensive effects showed that all these compounds could decrease blood pressure in a dose dependent manner on spontaneously hypertensive rats. And compound 2-(4-((2-butyl-4-methyl-6-(oxazolo[4, 5- b ]pyridine-2-yl)benzimidazole-1-yl)methyl)-1 H -indol-1-yl) benzoic acid (1f ), showed efficient and long-lasting effects in reducing blood pressure, with a maximal response lowered 55.98 ± 4.74 mmHg at 10 mg kg −1 and 35.82 ± 6.20 mmHg at 5 mg kg −1, the antihypertensive effect of it lasted beyond 24 h which was better than telmisartan. In the single-dose pharmacokinetic experiments, compound1f was absorbed efficiently and metabolized smoothly in Wistar rats. The values of C max, T max, AUC0–72, MRT0–72 and T 1/2 were 17.92 ± 10.85 ng mL −1, 2.60 ± 3.05 h, 252.85 ± 144.59 ng mL −1 h, 18.75 ± 0.43 h and 17.16 ± 4.24 h respectively. Compound1f was distributed into tissues rapidly and extensively after oral administration and the level of it was the highest in the liver, followed by in the kidney, and the lowest in brain. The acute toxicity assays in ICR rats of1f showed that it had low acute toxicity with an LD50 value of 1459.89 mg kg −1 . These encouraging results make1f an efficient, long-acting and safe antihypertensive drug candidate and deserving of further investigation.